THE EFFECT OF GROUP INVESTIGATION METHOD TOWARDS STUDENTS SPEAKING COMPETENCE BASED ON STUDENTS SELF-CONFIDENCE AT SMAN 1 SAKRA TIMUR IN ACADEMIC YEAR 2017/2018 - Imansyah Imansyah; Maya Atmi Primandari (Mandala, 2018)
This research aimed to find out the eeffect of group investigation method towards students speaking competence based on students’ self-confidence at SMAN 1 SAKRA TIMUR In Academic Year 2017/2018. This research was designed as experimental research by employing two way anova as the method of analyzing the data. The population of the study was the eleventh grade students at SMAN 1 Sakra Timur that consist of 2 classes, all of the classes were chosen as the samples, those were XI IPA 1 as experimental group that treated by using group investigation method and control group treated by using direct method. The data of the research were gathered from pre-test and post-test and the data analysis used TWO WAY ANOVA. Based on analysis of the data, it was found that the value of DK between coloum with the value of Fh=11,92 > F table=3,23 ,coloum DK within group with the value of Fh=4,19 > F table=4,09 , and the coloum of DK interaction with the value of Fh=19,85 > F table =3,23. It means Ha was accepted. It can be concluded that Group Investigation was effective towards students speaking competence based on students self-confidence at SMAN 1 SAKRA TIMUR.